Boundary spanning R&D collaboration: Key enabling technologies and missions as alleviators of proximity effects? - Matthijs J. Janssen; Milad Abbasiharofteh (Technological Forecasting and Social Change, 2022)
Two main targets of contemporary preferential innovation policy support, especially in Europe, are key enabling technologies (KETs) and innovation 'missions' focused on solving societal challenges. Both topics are associated with uniting disparate sets of capabilities, either by driving technology-based innovation into various application domains or by eliciting interdisciplinary and cross-sectoral solutions to urgent societal demands. In this study we assess to what extent pre-commercial R&D collaborations span geographic and cognitive boundaries. We analyze firm-level tie formation in Dutch collaborative R&D projects initiated in the period 2013–2018. Gravity models reveal that, while results for geographic proximity are mixed, some KET types are indeed related to projects in which cognitive proximity is significantly less relevant for tie formation. This contrasts with the findings for projects that retroactively received a mission label. Projects on health and care missions, and especially energy transition and sustainability missions, instead spur collaborations between cognitively proximate firms. The latter suggests that without additional policy intervention, such projects might interconnect similar rather than dissimilar knowledge bases. We conclude by discussing research and policy implications.
Keywords: O31; O38; 300; innovation policy; societal challenges; general purpose technologies; proximity dimensions; networks